2019
DOI: 10.1038/s41598-019-44376-z
|View full text |Cite
|
Sign up to set email alerts
|

Breast-lesions characterization using Quantitative Ultrasound features of peritumoral tissue

Abstract: The presented studies evaluate for the first time the efficiency of tumour classification based on the quantitative analysis of ultrasound data originating from the tissue surrounding the tumour. 116 patients took part in the study after qualifying for biopsy due to suspicious breast changes. The RF signals collected from the tumour and tumour-surroundings were processed to determine quantitative measures consisting of Nakagami distribution shape parameter, entropy, and texture parameters. The utility of param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 49 publications
3
35
0
1
Order By: Relevance
“…According to the literatures, the use of morphological features and texture features is not limited to the diagnosis of benign and malignant diseases, and these features also help classify malignant tumour subtypes [13,15,[17][18][19]. and malignant lesions, which is consistent with the literature [11].…”
Section: Discussionsupporting
confidence: 81%
“…According to the literatures, the use of morphological features and texture features is not limited to the diagnosis of benign and malignant diseases, and these features also help classify malignant tumour subtypes [13,15,[17][18][19]. and malignant lesions, which is consistent with the literature [11].…”
Section: Discussionsupporting
confidence: 81%
“…Morphological and texture features are the main factors for AI diagnosis. According to the literature, the use of morphological features and texture features is not limited to the diagnosis of benign and malignant diseases, and these features also help classify malignant tumour subtypes [6,13,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Kilmonda et al . have also found that QUS features can be used to characterize breast imaging, reporting and data system scores in breast tissue [ 16 ]. Measurements of the backscatter coefficient (BSC) and other parameters have been used to diagnose liver disease with 87% sensitivity in a cohort of 204 patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%